Endothelial Transient Receptor Potential Channels and Vascular Remodeling: Extracellular Ca2 + Entry for Angiogenesis, Arteriogenesis and Vasculogenesis - Negri, Sharon; Faris, Pawan; Berra-Romani, Roberto; Guerra, Germano; Moccia, Francesco (Frontiers in Physiology, 2020)
Vasculogenesis, angiogenesis and arteriogenesis represent three crucial mechanisms involved in the formation and maintenance of the vascular network in embryonal and post-natal life. It has long been known that endothelial Ca2+ signals are key players in vascular remodeling; indeed, multiple pro-angiogenic factors, including vascular endothelial growth factor, regulate endothelial cell fate through an increase in intracellular Ca2+ concentration. Transient Receptor Potential (TRP) channel consist in a superfamily of non-selective cation channels that are widely expressed within vascular endothelial cells. In addition, TRP channels are present in the two main endothelial progenitor cell (EPC) populations, i.e., myeloid angiogenic cells (MACs) and endothelial colony forming cells (ECFCs). TRP channels are polymodal channels that can assemble in homo- and heteromeric complexes and may be sensitive to both pro-angiogenic cues and subtle changes in local microenvironment. These features render TRP channels the most versatile Ca2+ entry pathway in vascular endothelial cells and in EPCs. Herein, we describe how endothelial TRP channels stimulate vascular remodeling by promoting angiogenesis, arteriogenesis and vasculogenesis through the integration of multiple environmental, e.g., extracellular growth factors and chemokines, and intracellular, e.g., reactive oxygen species, a decrease in Mg2+ levels, or hypercholesterolemia, stimuli. In addition, we illustrate how endothelial TRP channels induce neovascularization in response to synthetic agonists and small molecule drugs. We focus the attention on TRPC1, TRPC3, TRPC4, TRPC5, TRPC6, TRPV1, TRPV4, TRPM2, TRPM4, TRPM7, TRPA1, that were shown to be involved in angiogenesis, arteriogenesis and vasculogenesis. Finally, we discuss the role of endothelial TRP channels in aberrant tumor vascularization by focusing on TRPC1, TRPC3, TRPV2, TRPV4, TRPM8, and TRPA1. These observations suggest that endothelial TRP channels represent potential therapeutic targets in multiple disorders featured by abnormal vascularization, including cancer, ischemic disorders, retinal degeneration and neurodegeneration.